Evaluation of frequency of antibodies against Neospora caninum, Toxoplasma gondii and Brucella melitensis, risk factors and spatial distribution of infection in goat and sheep flocks from Argentina - Novoa, María Belén; Aguirre, Nerina; Ormaechea, Nadia; Palmero, Sebastian; Valentini, Beatriz Susana; Vanzini, Victor Rene; Molineri, Ana Ines (Elsevier, 2024)
Neospora caninum, Toxoplasma gondii and Brucella melitensis are pathogens that cause abortion in small ruminants. Besides, B. melitensis and T. gondii are zoonotic pathogens. The aim of this study was to describe the frequency of antibodies against N. caninum, T. gondii and B. melitensis in sheep and goats from three provinces of the center region of Argentina. In addition, the spatial distribution of the infected flocks/herds and risk factors were evaluated. A cross-sectional study was conducted from 2015 through 2016. Serum samples from 4783 goats and 1524 sheep from 186 goat, 51 sheep and 38 mixed flocks/herds were analyzed. Competitive inhibition enzyme-linked immunosorbent assay (ciELISA) and indirect fluorescent antibody test (IFAT) were performed for detection of antibodies against N. caninum and IFAT for T. gondii. The buffered plate antigen test and complement fixation test were performed for detection of antibodies against B. melitensis. The frequency of anti-T. gondii antibodies was 41.2% and 29.7% for sheep and goats, respectively. The frequency of anti-N. caninum antibodies was 17.2% and 14% for sheep and goats, respectively. About 97.1% of the sheep flocks, 79.4% of the goat herds and the 91.3% of the mixed flocks had seropositive animals to T. gondii. About 61.8% of the sheep flocks, 58% of the goat herds and the 82.6% of the mixed flocks had seropositive animals to N. caninum. All the analyzed animals were negative to anti-B. melitensis antibodies. For T. gondii, a significant cluster of high risk of seropositive flocks/herds was detected in the littoral of the Parana River. The province of origin of the flock/herd was the only variable associated to T. gondii positivity (p = 0.003). Animals from Santiago del Estero and Santa Fe Provinces had 3.48 and 1.77 times more risk to be positive to T. gondii than animals from Entre Ríos Province, respectively. For N. caninum, a cluster of high risk of seropositive flocks/herds was detected in the north of Santa Fe Province. The only explanatory variable associated to N. caninum positivity was animal species (p = 0.003). Sheep had 1.73 times more risk to be positive to N. caninum than goats. The absence of antibodies against B. melitensis in all the analyzed animals is an important finding for the public health of the region. Since bordering provinces have infected flocks/herds, brucellosis in small ruminants should be under epidemiologic surveillance in the region.